2022
DOI: 10.1371/journal.pgph.0000214
|View full text |Cite
|
Sign up to set email alerts
|

“Separated during the first hours”—Postnatal care for women and newborns during the COVID-19 pandemic: A mixed-methods cross-sectional study from a global online survey of maternal and newborn healthcare providers

Abstract: Routine postnatal care (PNC) allows monitoring, early detection and management of complications, and counselling to ensure immediate and long-term wellbeing of mothers and newborns; yet effective coverage is sub-optimal globally. The COVID-19 pandemic disrupted availability and quality of maternal and newborn care despite established guidelines promoting continuity of essential services. We conducted a cross-sectional global online survey of 424 maternal and newborn healthcare providers from 61 countries, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…However, there was a greater reduction in low-income countries compared to high-income countries. The provision of breastfeeding support was however reduced more in high-income countries compared to low-income countries [32] . Other reductions in PNC content included mental health counseling and support to women, newborn weight monitoring, and newborn vaccination [33] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there was a greater reduction in low-income countries compared to high-income countries. The provision of breastfeeding support was however reduced more in high-income countries compared to low-income countries [32] . Other reductions in PNC content included mental health counseling and support to women, newborn weight monitoring, and newborn vaccination [33] .…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Semaan et al (2022), which was not included in our review, also revealed that slightly more than a quarter of the respondents perceived a reduction in the number of women and newborns attending outpatient PNC services. Semaan et al (2022) also reported that women’s poor experiences while in the hospital were caused by a reduction in the number of visitors, banning of visitors altogether, and shortening of visiting hours [32] . Since the utilization of PNC services was reduced, to ensure that mothers and newborns receive PNC, other strategies need to be devised.…”
Section: Discussionmentioning
confidence: 99%
“…This was in addition to general lockdown policies limiting movement, work, transport and, more specifically in the health sector, reassignment of various health workers to COVID‐19‐related duties. In maternity care services, 7 contrary to the WHO/UNICEF Baby‐Friendly Hospital Initiative guidance, some of these restrictions included excluding a companion of choice and not allowing family members to visit, separation of mothers and newborns (even where COVID‐19 had not been suspected), and discouraging breastfeeding 8–10 …”
Section: Domain Number Of Questionsmentioning
confidence: 99%
“…In maternity care services, 7 contrary to the WHO/ UNICEF Baby-Friendly Hospital Initiative guidance, some of these restrictions included excluding a companion of choice and not allowing family members to visit, separation of mothers and newborns (even where COVID-19 had not been suspected), and discouraging breastfeeding. [8][9][10] In addition, key dimensions of experience of care such as patient participation, provision of emotional support, and attempts to reduce certain interventionist procedures of limited clinical value, were among the first aspects of care to be sidelined during the pandemic. 11 Although emotional support is widely recognized as being important to patient experiences and recovery, 12 many health authorities or facilities did not allow companions of choice or visits from family members, and some facilities routinely separated infants from parents in a, likely ineffective, effort to reduce transmission risk.…”
Section: Imagine Euro: Data For Action On Quality Of Maternal and New...mentioning
confidence: 99%
See 1 more Smart Citation